A handbook of Middle English studies - Turner, Marion, 1976- (Wiley-Blackwell, A John Wiley & Sons, Ltd., Publication, 2013)
"A Handbook to Middle English Studies presents a series of original essays from leading literary scholars that explore the relationship between critical theory and late medieval literature. This book: Includes 26 new essays by leading scholars of late medieval literature ; Sets the new standard for an introduction to the study of late medieval literature ; Showcases the most current cutting-edge theoretical research ; Demonstrates a range of approaches to late medieval literature ; Brings together critical theory and medieval literature."--Publisher's website.